Пути улучшения характеристик магнетронных генераторов для систем радиолокации и связи - Чурюмов, Г. И.; Одаренко, Е. Н.; Фролова, Т. И.; Старчевский, Ю. Л.; Васянович, А. В.; Иванцов, В. П.; Экезли, А. И.; Сивоконь, К. В. (ХНУРЭ, 2009)
The results of an experimental investigation of the factors cause of frequency instability in the magnetrons are described. Introduce a phenomenological description of frequency fluctuation concept in magnetrons. The investigation results of the anode block temperature effect on the frequency and a power supply disturbances on the magnetron stability.
Keywords: магнетронный генератор; система радиолокации